Katılım Bankacılığında Kredilerin Yapılandırılması: Metal Borsası Perspektifinden Bir İnceleme / Credit Restructuring in Participation Banking: An Examination from Perspective of Metal Exchange - Kartal, Mustafa Tevfik (Journal of History Culture and Art Research, 2018)
Abstract Credits have become the most important asset item in the participation banking which has been going on to growth in Turkey. Credits have reached level of TL 106 billion at the end of 2017 whereas it was level of TL 41 billion at the end of 2011. Shares of credits in total assets have occurred as 66.6% at the end of 2017 whereas 7it was as 73.2% at the end of 2010. On the other hand, increases in nonperforming credits have been seen with the credits’ growth. Net nonperforming credits have reached level of TL 992 million at the end of 2017 whereas it was level of TL 430 million at the end of 2011. Therefore, it is important that credits are restructured before follow-up stage. This study is prepared to examine credit restructuring in participation banking which have reached to an important amount. In the study, restructuring of credits in participation banking is examined in view of metal exchange. It has been defined that credit restructuring transactions are carried out at high level in participation banking; London Metal Exchange (LME) is used for these transactions; transaction volume at billion TL is occurred abroad; commission at million USD is paid to abroad. As a result of the study, establishment of a metal market, which has LME standards and characteristics, in Borsa İstanbul (BIST) is recommended. With the realization of the recommendation, credit restructuring process of participation banks will be shortened, the transaction volume at billion TL paid abroad will be attracted to the domestic market, commissions at million USD be kept in the domestic market, financial markets will be diversified, hence contribution will be provided to participation banking and Turkish Banking Sector. Öz Türkiye’de büyümesi devam eden katılım bankacılığında krediler en önemli varlık kalemi haline gelmiştir. 2011 sonunda 41 milyar TL seviyesinde olan krediler 2017 yılsonunda 106 milyar TL seviyesine ulaşmıştır. Katılım bankacılığında kredilerin aktif toplam içindeki payı 2011 yılında %73,2 seviyesindeyken 2017 yılsonunda %66,6 olarak gerçekleşmiştir. Diğer taraftan kredilerin artışı ile birlikte takipteki kredilerde artış görülmektedir. 2011 yılsonunda 430 milyon TL seviyesinde olan net takipteki krediler 2017 yılsonunda 992 milyon TL seviyesine ulaşmıştır. Dolayısı ile kredilerin takip aşamasına gelmeden yapılandırılması önem taşımaktadır. Bu çalışma katılım bankacılığında önemli tutarlara ulaşan kredi yapılandırma faaliyetlerinin incelenmesine yönelik hazırlanmıştır. Çalışmada katılım bankacılığında kredilerin yapılandırılması metal borsası perspektifinden incelenmiştir. Katılım bankacılığında yüksek tutarda kredi yapılandırma işlemlerinin yapıldığı, bu işlemlerde Londra Metal Borsası’nın (LMB) kullanıldığı, milyar TL seviyesinde işlem hacminin yurtdışında gerçekleştiği ve milyon dolar seviyesinde komisyonun yurt dışına ödendiği belirlenmiştir. Çalışma sonucunda Borsa İstanbul (BİST) bünyesinde LMB standartlarına ve özelliklerine sahip bir metal piyasası kurulması önerilmiştir. Bu önerinin hayata geçmesi ile birlikte katılım bankalarının kredi yapılandırma süreçleri kısalacak, yurtdışında gerçekleştirilen milyar TL’lik işlem hacmi yurtiçine çekilecek, yurtdışına ödenen milyon dolarlık aracı komisyonları yurt içinde kalacak, finansal piyasalar çeşitlendirilecek, dolayısıyla katılım bankacılığına ve Türk Bankacılık Sektörüne katkı sağlanacaktır.